SAINTE AGNÈS: VERSIONE ANONIMA FRANCESE (BnF, fr. 1553). - Solla, Beatrice (Estudios Románicos, 2017)
This paper will discuss the Vie de Sainte Agnès, a hagiographic narrative text in décasyllabes monorimes of the late 13th century, preserved exclusively in manuscript BnF: Fr. 1553. This paper aims to investigate literary sources and their re-elaborations in an attempt to seize all the peculiarities of the text. It will also analyze the poem in relation to the manuscript context, and will propose a hypothesis about possible authorship, as well as providing a !rst examination of the language, to point some typical features of the scripta.